TYPES OF ASSESSMENT - Nazarova Durdona Fayzulla qizi Student Gaziyeva Saida Turgunovna (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
Assessment is a cornerstone of effective teaching and learning. It helps educators gauge the extent of student understanding, guide instruction, and provide feedback that supports academic development. This article explores the various types of assessment used in modern education systems, with a focus on formative, summative, diagnostic, and ipsative assessments. Each of these serves unique functions in the classroom, from tracking initial knowledge to evaluating cumulative learning outcomes. The study employs qualitative methods, including literature analysis and interviews with practicing teachers, to evaluate how these assessment types are applied in real-world contexts. The findings reveal that a strategic blend of assessment types fosters a more holistic approach to evaluating and improving student learning. The article also discusses the practical challenges educators face and emphasizes the need for professional development to implement assessments effectively.